Podnikatelský záměr rozvoje firmy - Skácel, Petr (Vysoké učení technické v Brně. Fakulta podnikatelská, 2009)
Diplomová práce se zabývá analýzou problému současného stavu firmy IVANA ČECHOVÁ. Úvodní část je věnována charakteristice zkoumaného podniku a je doplněna o teoretická východiska práce. Praktická část je zaměřena na analýzu problémů a soudobé situace firmy, z kterých jsou stanoveny hlavní nedostatky rozvoje. Vlastní návrh zlepšení představuje podnikatelský záměr firmy IVANA ČECHOVÁ. Součástí práce je také posouzení rozšíření podnikatelského záměru se zaměřením na možnost financování z fondů Evropské unie.

This diploma thesis is focused on the present situation analyse of the company IVANA ČECHOVÁ. The begining part contains the characteristic of the analysed company and the theoretically resources. The practicall part is focused on the company problems and present situation analyse, from which the most significant lacks of business developement are determined. The improvement proposal represents the entrepreneurial intension of the company IVANA ČECHOVÁ. The examination of the entrepreneurial intension aimed at European funds is in this thesis mentioned too.
Entrepreneurial Intention of Business Development
Keywords: Podnikatelský plán; finanční analýza; rozvoj podniku; fondy Evropské unie; dotace; zemědělství; obnovitelné zdroje energie.; Business plan; Financial analysis; Company development; European Union funds; grants; agriculture; Renewable resourses of energy.